Konsep Ruang Ume Kbubu Desa Kaenbaun Kabupaten Timor Tengah Utara - Thomas Kurniawan Dima; Antariksa Antariksa; Agung Murti Nugroho (RUAS (Review of Urbanism and Architectural Studies), 2013)
Kaenbaun village is a village that is inhabited by some of the tribes are divided into two groups, male and female. The traditional house of this village, ume kbubu, plays an important role for the people of Kaenbaun. The objective of this study was to investigatethe concept of space as one of the local wisdom in kaenbaun village, using descriptive analitycal method. This research analysed spaces in four type of single-columned ume kbubu. The result showed the concept space in ume kbubu formed by existing activities. In all four types of ume kbubu, there are some concepts of space remaining constant such as cooking area which is always located on the back of the room, the rest area on the left or right side of the room, area of traditional rituals placed in the middle, transitional area in the front porch, and outdoor spaces area.Keywords: Ume Kbubu, Kaenbaun Village, Concept of space